If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(2x) + log(3x) = log(96) Remove parenthesis around (2x) glo * 2x + log(3x) = log(96) Reorder the terms for easier multiplication: 2glo * x + log(3x) = log(96) Multiply glo * x 2glox + log(3x) = log(96) Remove parenthesis around (3x) 2glox + glo * 3x = log(96) Reorder the terms for easier multiplication: 2glox + 3glo * x = log(96) Multiply glo * x 2glox + 3glox = log(96) Combine like terms: 2glox + 3glox = 5glox 5glox = log(96) Reorder the terms for easier multiplication: 5glox = 96glo Solving 5glox = 96glo Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-96glo' to each side of the equation. -96glo + 5glox = 96glo + -96glo Combine like terms: 96glo + -96glo = 0 -96glo + 5glox = 0 Factor out the Greatest Common Factor (GCF), 'glo'. glo(-96 + 5x) = 0Subproblem 1
Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-96 + 5x)' equal to zero and attempt to solve: Simplifying -96 + 5x = 0 Solving -96 + 5x = 0 Move all terms containing g to the left, all other terms to the right. Add '96' to each side of the equation. -96 + 96 + 5x = 0 + 96 Combine like terms: -96 + 96 = 0 0 + 5x = 0 + 96 5x = 0 + 96 Combine like terms: 0 + 96 = 96 5x = 96 Add '-5x' to each side of the equation. 5x + -5x = 96 + -5x Combine like terms: 5x + -5x = 0 0 = 96 + -5x Simplifying 0 = 96 + -5x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 9/5(191.8) | | 4y-20x=8 | | (3x-4z)(x-7z)= | | 108x+4=13+46x-2 | | 35=m^2-2m | | -2x^2+8x-7=0 | | (y-7)-y=6 | | 4(v-7)+2v=8 | | 23+3y-2=14y-14-4y | | (3/7)-(x/4)=1/28 | | x-(y-z+2)= | | (2x^2)+16x+22=0 | | 2(x+4)(3x+1)= | | 12+0.25=20.05 | | a+(-b-c)= | | 450-2X+X^2=0 | | 2(x+4)(3x+1)=0 | | 2x^2-8x-120= | | 108x+4=59x-2 | | (2t-4)/(t^2-4) | | 4x-5(4)=20 | | 6x+2=122 | | X^2-30x+207=0 | | (11z-2)(10z+9)=0 | | 24x^2-4x^3=0 | | (X^2+3x)-(x+4)(3x+8)=(3x+8)(x+3) | | (3b-4)-(-5b+3)= | | 2.4/3 | | 5x^2-8x+4=628 | | ln*4+ln*x=ln*7+ln(2x-2) | | 19=17-2x+5x | | 5-2x=3+2x+2 |